Metafora smogu informacyjnego a procesy informacyjne - Szynkiewicz, Mariusz (Wydawnictwo Naukowe UAM, 2014)
The author of this article investigates an epistemological problem that is related to information overload and the data smog metaphor in particular. The paper is focused on two aspects of data smog: the quantitative aspect, which concerns information dispersal, and the qualitative aspect, pertaining to the value of information.
The Data Smog Metaphor and Information Processes
Keywords: data smog; Internet; information overload; epistemology